Fixed‐dose combination ezetimibe+atorvastatin lowers LDL‐C equivalent to co‐administered components in randomized trials: use of a dose–response model. (27th February 2015) - Bays, Harold E.; Chen, Erluo; Tomassini, Joanne E.; McPeters, Gail; Polis, Adam B.; Triscari, Joseph
Abstract: Co‐administration of ezetimibe with atorvastatin is a generally well‐tolerated treatment option that reduces LDL‐C levels and improves other lipids with greater efficacy than doubling the atorvastatin dose. The objective of the study was to demonstrate the equivalent lipid‐modifying efficacy of fixed‐dose combination (FDC) ezetimibe/atorvastatin compared with the component agents co‐administered individually in support of regulatory filing. Two randomized, 6‐week, double‐blind cross‐over trials compared the lipid‐modifying efficacy of ezetimibe/atorvastatin 10/20 mg ( n = 353) or 10/40 mg ( n = 280) vs. separate co‐administration of ezetimibe 10 mg plus atorvastatin 20 mg ( n = 346) or 40 mg ( n = 280), respectively, in hypercholesterolemic patients. Percent changes from baseline in LDL‐C (primary endpoint) and other lipids (secondary endpoints) were assessed by analysis of covariance; triglycerides were evaluated by longitudinal‐data analysis. Expected differences between FDC and the corresponding co‐administered doses were predicted from a dose–response relationship model; sample size was estimated given the expected difference and equivalence margins (±4%). LDL‐C‐lowering equivalence was based on 97.5% expanded confidence intervals (CI) for the difference contained within the margins; equivalence margins for other lipids were not prespecified. Ezetimibe/atorvastatin FDC 10/20 mg was equivalent to co‐administered ezetimibe+atorvastatin 20 mg in reducing LDL‐C levels (54.0% vs. 53.8%) as was FDC 10/40 mg and ezetimibe+atorvastatin 40 mg (58.9% vs. 58.7%), as predicted by the model. Changes in other lipids were consistent with equivalence (97.5% expanded CIs <±3%, included 0); triglyceride changes varied more. All treatments were generally well tolerated. Hypercholesterolemic patients administered ezetimibe/atorvastatin 10/20 and 10/40 mg FDC had equivalent LDL‐C lowering. This FDC formulation proved to be an efficacious and generally well‐tolerated lipid‐lowering therapy.